ANALISIS KEPUASAN PELANGGAN PADA STASIUN KERETA API SEMARANG PONCOL (DAOP IV SEMARANG) - Trie Meisyah A; Herbasuki Nurcahyanto; Aufarul Marom (Journal of Public Policy and Management Review, 2015)
The background of this research began in the increasing needs ground transportation especially a train that are required will be the provision of good service in accordance with standard that has been set and meet customers expectations. A service provided can impact on customer satisfaction in the use of services in Semarang Poncol station. need of special attention from PT .Kereta Api Indonesia to make the quality of service at the Semarang Poncol station not stop and always been an increase in continuous. This research will know the level of customer satisfaction and indicators need to which priority to increase in Semarang Poncol station using descriptive quantitative. The total sample taken as many as 100 people customers using Semarang Poncol station service. This research using the measurement of satisfaction through five dimensions waiter namely the quality of tangible, reliability, responsiveness, assurance, and empathy by comparing between performance ( X ) and hope ( Y ) and cause to feel satisfied or dissatisfied. Based on the results of the tests the level of customer satisfaction there were seven out of twenty three indicators that are considered important in determining the satisfaction of customers who have high interest but in the implementation level low that can be found the level of customer satisfaction to very unsatisfactory until unsatisfactory. These indicators seventh among other: 1. the lounge facilities, 2. the toilet facilities, 3. the place of worship facilities, 4. the facilities up and down train carriages ( train ), 5. the facilities of disabled people, 6. the accuracy of the arrival and departure train, 7. the speed and the readiness of the officers in providing services , while in the fifth dimension that have low level of satisfaction is a tangible dimension get 73,32 % assessment (unsatisfactory) .